Transgenic Insights Linking Pitx2 and Atrial Arrhythmias - Franco, Diego (Frontiers in Physiology, 2012)
Pitx2 is a homeobox transcription factor involved in left–right signaling during embryogenesis. Disruption of left–right signaling in mice within its core nodal/lefty cascade, results in impaired expression of the last effector of the left–right cascade, Pitx2, leading in many cases to absence or bilateral expression of Pitx2 in lateral plate mesoderm (LPM). Loss of Pitx2 expression in LPM results in severe cardiac malformations, including right cardiac isomerism. Pitx2 is firstly expressed asymmetrically in the left but not right LPM, before the cardiac crescent forms, and subsequently, as the heart develops, becomes confined to the left side of the linear heart tube. Expression of Pitx2 is remodeled during cardiac looping, becoming localized to the ventral portion of the developing ventricular chambers, while maintaining a distinct left-sided atrial expression. The importance of Pitx2 during cardiogenesis has been illustrated by the complex and robust cardiac defects observed on systemic deletion of Pitx2 in mice. Lack of Pitx2 expression leads to embryonic lethality at mid-term, and Pitx2-deficient embryos display isomeric hearts with incomplete closure of the body wall. However, whereas the pivotal role of Pitx2 during cardiogenesis is well sustained, its putative role in the fetal and adult heart is largely unexplored. Recent genome-wide association studies have identified several genetic variants highly associated with atrial fibrillation (AF). Among them are genetic variants located on chromosome 4q25 adjacent to PITX2. Since then several transgenic approaches have provided evidences of the role of the homeobox transcription factor PITX2 and atrial arrhythmias. Here, we review new insights into the cellular and molecular links between PITX2 and AF.